Thematic and Metafunctional Insights into Singaporean English: A Study of Syntax and Dialect Formation - Yevis Haritsyah (Universitas Muhammadiyah Tapanuli Selatan, 2026)
The multilingual linguistic context in Singapore has been instrumental towards the evolution of Singapore Colloquial English (Singlish), a local form of the English language, which is used largely in informal communication. Due to the long-term interaction of English with other languages used in Singapore (such as Malay, Mandarin, Hokkien, and Tamil), Singlish exhibits unusual syntactic and discourse-related features that make it different to the Standard English. This research paper will examine the syntactic constructions and theme structure of Singaporean English in terms of the analytical tool of Systemic Functional Linguistics (SFL) with the focus to the ideational, interpersonal and textual metafunctions. The study is intended to determine the unique syntactic constructions defining Singlish, analyze the ways of realization of thematic structures in the discourse level as well as the way that these characteristics of language demonstrate the mechanisms of dialect formation in a multilingual environment. The study deconstructs data obtained through semi-structured interviews with Singaporean speakers who commonly use Singlish in daily communication with others with the help of a qualitative descriptive design. Some hundred clauses with important syntactic characteristics were transcribed and analysed using a syntactic and metafunctional analysis, such as ThemeRheme structure, transitivity patterns and mood structures. The results indicate that there are a number of repetitive grammatical patterns such as ellipsis and grammatical reduction, deletion of copula, topic-prominent constructions, simplified tense marking and sentence-final discourse particles. These characteristics show that Singlish syntax is characterized by the structural simplification and functional adaptation to the multilingual sociolinguistic context in Singapore. The paper finds that Singaporean English is a systematic contact variety whose grammar patterns have a strong relationship with thematic organization and metafunctional meaning-making practices in language.